Hukum dan Tanggung Jawab dalam Praktik Kedokteran di Rumah Sakit Universitas Indonesia Timur - Esa, Ambo (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
This study aims to examine in depth the legal aspects and forms of professional responsibility in medical practice that takes place at the University of East Indonesia Hospital, an academic hospital that integrates service, education, and research functions. The main focus of the study is to understand the extent to which medical personnel (doctors and nurses) understand and apply laws and regulations such as Law No. 29 of 2004 concerning Medical Practice, the Indonesian Code of Medical Ethics (KODEKI), and the principles of informed consent in interactions with patients. This study uses a mixed method, namely a quantitative approach through questionnaires and a qualitative approach through in-depth interviews and analysis of medical documents. The results of the study indicate that the level of legal understanding of medical personnel is quite high, but various obstacles were found in the implementation of legal responsibility such as lack of adequate medical documentation, inconsistencies in the informed consent process, and the lack of an open and accountable medical incident reporting system. These findings indicate the importance of strengthening health law training for medical personnel, increasing awareness of ethical and legal responsibilities, and developing an effective audit and reporting system as an effort to protect patient rights as well as legal protection for medical personnel. This study is expected to be a reference for hospital management and medical education institutions in designing policies and training programs that support responsible and legal medical practices.